Hydrothermal liquefaction of Gracilaria gracilis and Cladophora glomerata macro-algae for biocrude production. (February 2018) - Parsa, Mehran; Jalilzadeh, Hamoon; Pazoki, Maryam; Ghasemzadeh, Reza; Abduli, MohammadAli
Highlights: Two Caspian Sea macroalgae were converted to biocrude by HTL conversion. Red macroalgae has high biocrude HHV, 36 Mj/kg. The formation pathways of biocrude compounds were studied. HTL aqueous residue recycle significantly increases biocrude yields. Abstract: The potential of Gracilaria gracilis (G. gracilis) and Cladophora glomerata (C. glomerata) macro-algae species harvested from Caspian Sea for biocrude oil production under Hydrothermal Liquefaction (HTL) reaction at 350 °C and 15 min has been investigated. Furthermore, the effect of using recycled aqueous phase as the HTL reaction solvent was studied. The biocrude yield for G. gracilis and C. glomerata was 15.7 and 16.9 wt%, respectively with higher heating value (HHV) of 36.01 and 33.06 MJ/kg. The sources of each existing component in bio-oil were identified by GC–MS based on their suggested reaction pathways. Moreover, after two series of aqueous solution recycling, experiments showed that the bio-oil yield significantly increased compared with the initial condition. This increasing directly relates with recovery of carbon content from the aqueous solution residue.